Olexandr Ivanovych Bodnia - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to Alexander Ivanovich, Doctor of Medical Sciences, Professor of the Department of Traumatology and Orthopedics, Odessa National Medical University.